Macrocyclic factor XIa inhibitors. Issue 17 (1st September 2017) - Wang, Cailan; Corte, James R.; Rossi, Karen A.; Bozarth, Jeffrey M.; Wu, Yiming; Sheriff, Steven; Myers, Joseph E.; Luettgen, Joseph M.; Seiffert, Dietmar A.; Wexler, Ruth R.; Quan, Mimi L.
Graphical abstract: Abstract: A series of macrocyclic factor XIa (FXIa) inhibitors was designed based on an analysis of the crystal structures of the acyclic phenylimidazole compounds. Further optimization using structure-based design led to inhibitors with pM affinity for FXIa, excellent selectivity against a panel of relevant serine proteases, and good potency in the activated partial thromboplastin time (aPTT) clotting assay.